2010
DOI: 10.1152/ajpgi.00246.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol consumption enhances sensitivity to Ca2+-mediated opening of the mitochondrial permeability transition pore and increases cyclophilin D in liver

Abstract: King AL, Swain TM, Dickinson DA, Lesort MJ, Bailey SM. Chronic ethanol consumption enhances sensitivity to Ca 2ϩ -mediated opening of the mitochondrial permeability transition pore and increases cyclophilin D in liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 81 publications
7
29
0
Order By: Relevance
“…Previously, we reported that chronic ethanol consumption increased CypD at gene and protein levels in liver, whereas other proposed MPT pore components, including the adenine nucleotide translocator (ANT), remained unchanged (47). We also observed that chronic ethanol consumption enhanced sensitivity to Ca 2ϩ -dependent opening of the MPT pore in isolated rat liver mitochondria (47). These data suggest that increased CypD levels may predispose liver mitochondria to undergo MPT pore formation and opening in response to chronic ethanol consumption.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Previously, we reported that chronic ethanol consumption increased CypD at gene and protein levels in liver, whereas other proposed MPT pore components, including the adenine nucleotide translocator (ANT), remained unchanged (47). We also observed that chronic ethanol consumption enhanced sensitivity to Ca 2ϩ -dependent opening of the MPT pore in isolated rat liver mitochondria (47). These data suggest that increased CypD levels may predispose liver mitochondria to undergo MPT pore formation and opening in response to chronic ethanol consumption.…”
mentioning
confidence: 58%
“…These findings suggest that CypD-dependent regulation of the MPT pore may play a crucial role in cellular responses to stresses relevant to human disease, especially diseases induced by Ca 2ϩ overload and oxidative stress. Previously, we reported that chronic ethanol consumption increased CypD at gene and protein levels in liver, whereas other proposed MPT pore components, including the adenine nucleotide translocator (ANT), remained unchanged (47). We also observed that chronic ethanol consumption enhanced sensitivity to Ca 2ϩ -dependent opening of the MPT pore in isolated rat liver mitochondria (47).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Chronic EtOH exposure in rats leads to sustained Ca 2+ elevation that triggers MPTP opening. MPTP opening leads to Ca 2+ overload in the mitochondria and results in mitochondrial swelling a phenomenon observed in EtOH fed rats but not in control rats (45). Cells at basal metabolic rate tightly regulate free Ca 2+ in the range of 100 to 200 nM in both cytosol and mitochondria through NCX (Na + /Ca 2+ exchanger), PMCA (Plasma membrane Ca 2+ -ATPase) and SERCA (Sarcoendoplasmic reticulum Ca 2+ -ATPase) pumps.…”
Section: Role Of Ethanol In Ros Productionmentioning
confidence: 99%
“…ER-mitochondria link and the mitochondrial Ca 2+ ([Ca 2+ ] m ) uptake through uniporter is known to promote [Ca 2+ ] m overload which subsequently leads to mitochondrial depolarization and increased mROS production (10,28,35,36). The aberrant Ca 2+ homeostasis has been linked with ALD (37,38). Despite the vast knowledge, the actual intricacies on the mechanism of Ca 2+ induced mitochondrial dysfunction remain largely unexplored.…”
mentioning
confidence: 99%